"Applying artificial intelligence techniques and their quantity to administrative decision-making" (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the impact of artificial intelligence (AI) applications on administrative decision-making in contemporary organizations. The study adopted a descriptive-analytical approach supported by a quantitative exploratory method based on field data collected from a purposive sample of (18) respondents working in administrative positions related to decision-making processes or the use of intelligent systems.A structured questionnaire was used, consisting of two main dimensions: the level of AI implementation and its impact on the quality, speed, and accuracy of administrative decision-making. Data were analyzed using SPSS, employing descriptive statistics, standard deviations, and Pearson correlation analysis.The findings revealed that the level of AI implementation in the studied organizations ranges between moderate and low, with partial use in decision support processes. The results also indicated a strong positive impact of AI on the quality of administrative decisions, particularly in improving accuracy, reducing errors, and enhancing objectivity. Moreover, AI significantly contributes to accelerating decision-making by improving data processing efficiency and reducing the time required to reach decisions.In addition, the study found strong positive correlations between AI adoption and both decision quality and decision speed, while an inverse relationship was observed with implementation challenges, particularly infrastructure limitations, lack of skilled personnel, and high costs. The study concluded that the effectiveness of AI in supporting administrative decision-making largely depends on organizational, technical, and human readiness.
Keywords: Artificial Intelligence, Administrative Decision-Making, Decision Support Systems, Digital Transformation, Decision Quality, Organizational Performance